If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5=p-(-10)
We move all terms to the left:
5-(p-(-10))=0
We calculate terms in parentheses: -(p-(-10)), so:We get rid of parentheses
p-(-10)
We add all the numbers together, and all the variables
p+10
Back to the equation:
-(p+10)
-p-10+5=0
We add all the numbers together, and all the variables
-1p-5=0
We move all terms containing p to the left, all other terms to the right
-p=5
p=5/-1
p=-5
| (6x+4)+(3x+1)+5x=1/2 | | 9r-7=187 | | -12=4f+6f | | x-4=2x-18` | | 3(l-6=15 | | 5/2x+1/2x=17.5+7/2x | | 90+z+130=180 | | 2y+1=y-5. | | -4=s-4 | | -4a+3+5a=11-25 | | m=234 | | −2=−4+t | | 11x+5=7x+41 | | 5+8=-13-2x | | 2x+6+135+25=180 | | 5/2k+8-11/2k=5k-4 | | 5=4-b | | 2m+2m=12 | | -21=-18x+33 | | 4x-8=5x+30 | | 38=3p+5 | | 5w=10=100 | | 16=2x+1-7 | | X^+2-3x+8=0 | | 28t^2-17t=0 | | 5=x+5,x=10 | | 2(v+16)=40 | | 9-2x-6x=62 | | 11x-17=65=180 | | 32x+5=44x-9 | | 8w−8=80 | | f/4-5=-5 |